2023
DOI: 10.1155/2023/3786342
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-Ankle Pulse Wave Velocity Mediates the Association between Increased Age and Risk of Sarcopenia among Chinese Patients with Type 2 Diabetes Mellitus

Abstract: Background and Aims. Arterial stiffness and sarcopenia are commonly seen in patients with type 2 diabetes mellitus (T2DM), and both are age-related diseases. However, few studies have addressed the causal relationship between age, arterial stiffness, and sarcopenia, especially in patients with T2DM. This study is aimed at investigating the relationship among age, arterial stiffness, and sarcopenia in patients with T2DM. Methods and Results. This cross-sectional study enrolled 557 inpatients with diabetes at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Higher brachia‐ankle PWV significantly correlates with physical frailty in older adults 82 . A recent study suggested that the ankle‐brachial PWV might be responsible for the association between aging and sarcopenia risk 83 . Low ABI similarly exhibits an association with poor functional status in the hospitalized older patients 84 …”
Section: Vascular Frailty: How To Operationalize?mentioning
confidence: 99%
“…Higher brachia‐ankle PWV significantly correlates with physical frailty in older adults 82 . A recent study suggested that the ankle‐brachial PWV might be responsible for the association between aging and sarcopenia risk 83 . Low ABI similarly exhibits an association with poor functional status in the hospitalized older patients 84 …”
Section: Vascular Frailty: How To Operationalize?mentioning
confidence: 99%